Evaluación de la producción de gas y líquido combustible mediante el proceso de pirólisis de madera para aplicación en la zona del resguardo Yaigojé en el Vaupés colombiano (2019)
The present research work seeks to evaluate the pyrolytic process of tropical woods, in order to establish in a proactive manner technical design specifications for the production of electric power from wet wood, for later application and benefit of two indigenous communities of the Yaigojé reservation in the Colombian Vaupés. For this, in the first instance, through a bibliographic review, the potential energy use of the wood is determined, as well as its possible transformation and conversion routes; From this, the physicochemical parameters of interest that must be taken into account to evaluate a biomastic source and the reason for the importance of their knowledge are determined in order to establish the influence of these parameters in the pyrolysis process. Subsequently, the characterization of 7 wood samples was carried out based on the parameters set in the previous step in order to know the main characteristics of the biomastic source to work and in this way to determine its influence on the pyrolysis process. As a step followed, the pyrolytic process of sampled tropical woods was carried out experimentally, as well as their respective pre-treatment processes through drying operations and reduction of particle size. Likewise, the yields of the process were established for the 3 main products of pyrolysis (solid, liquid and gas). Once the yields of the process have been quantified, the outgoing gas is characterized by gas chromatography in order to determine the composition of the gaseous compounds that are part of the gas mixture that leaves the process, as well as the determination of the power calorific of this mixture.